Njuah-Njuah cultural festival as a counter-hegemonic space for sustaining Pakpak traditional music in Dairi Regency - Tobing, Jakob P Cennedy Lumban; Nasution, Ikhwanuddin; Purba, Mauly (International Journal of Culture and Art Studies, 2026)
This study examines the shrinking cultural space of Pakpak traditional music in Dairi Regency, North Sumatra, where Batak Toba musical aesthetics increasingly dominate ritual, religious, and public cultural events. Although the Pakpak community possesses a rich musical tradition, particularly the Genderang Sisibah ensemble, these forms are gradually displaced within everyday communal practices. This research aims to analyze how the Njuah-Njuah Cultural Festival functions as a cultural arena that supports the sustainability and visibility of Pakpak traditional music. The study employs a qualitative ethnographic approach involving participant observation, in-depth interviews with cultural actors and musicians, and analysis of institutional and cultural documents. Fieldwork was conducted across several communal contexts, including family rituals, church activities, school events, entertainment markets, and the Njuah-Njuah Cultural Festival. The findings reveal that the dominance of Batak Toba music is not merely a matter of aesthetic preference but is closely tied to structural factors such as institutional influence, symbolic legitimacy, and the broader availability of Batak Toba musicians in the local entertainment economy. Despite these pressures, the Njuah-Njuah Cultural Festival provides an important public platform where Pakpak musical traditions regain visibility and cultural authority. The study contributes theoretically by demonstrating how cultural festivals can serve as counter-hegemonic arenas that facilitate the transmission, negotiation, and continuity of indigenous musical traditions in contemporary socio-cultural contexts.